Biobehavioral Intervention Targeting Physical Activity Behavior Change for Older Veterans after Nontraumatic Amputation: A Randomized Controlled Trial. Issue 10 (6th May 2020) - Christiansen, Cory L.; Miller, Matthew J.; Kline, Paul W.; Fields, Thomas T.; Sullivan, William J.; Blatchford, Patrick J.; Stevens‐Lapsley, Jennifer E.
Abstract : Background: Lower‐limb amputation (LLA) due to non‐traumatic vascular etiology is linked to extremely low physical activity and high disability. Objective: To test the feasibility of a biobehavioral intervention designed to promote physical activity. Design: A randomized, single‐blind feasibility trial with a crossover design. Setting: Veterans Administration Medical Center. Participants: Military veterans (age: 65.7 [7.8] years; mean [standard deviation]) with nontraumatic lower‐limb amputation (LLA), randomized to two groups: GROUP1 (n = 16) and GROUP2 (n = 15). Both groups had similar baseline amputation characteristics (level of amputation and time since amputation). Interventions: Twelve weekly, 30‐minute telehealth sessions of physical activity behavior‐change intervention, with GROUP1 participating in weeks 1‐12 and GROUP2 in weeks 13‐24. GROUP1 noncontact phase in weeks 13‐24 and GROUP2 attention control telehealth phase in weeks 1‐12. Main Outcome Measures: Feasibility (participant retention, dose goal attainment, intervention acceptability [Intrinsic Motivation Inventory [IMI] Interest and Enjoyment scale], safety) and signal of efficacy (free‐living physical activity [accelerometer‐based average daily step count], Late Life Function and Disability Index ‐ Disability Scale [LLFDI‐DS]). Results: Participant retention rate was high (90%), with three participants lost to follow‐up during the intervention period. Dose goal attainment was low, with only 10% of participants achieving an a priori walking dose goal. Intervention was rated as acceptable, with mean IMI Interest and Enjoyment score (5.8) statistically higher than the null value of 5.0 ( P = .002). There were no between‐group differences in adverse event rates (falls: P = .19, lower extremity wounds: P = .60). There was no signal of efficacy for change in average daily step count ( d = −0.15) or LLFDI‐DS ( d = −0.22 and 0.17 for frequency and limitations scales, respectively). Conclusions: Telehealth delivered biobehavioral intervention resulted in acceptable participant retention, low dose goal attainment, high participant acceptability, and low safety risk, while having no signal of efficacy (physical activity, disability) for people with nontraumatic LLA.